Prevalence and determinants of physical frailty among people living in residential aged care facilities: a large-scale retrospective audit - Rachel Milte; Jasmine Petersen; Jo Boylan; Tim Henwood; Sarah Hunter; Belinda Lange; Michael Lawless; Stacey Torode; Lucy K. Lewis (BMC Geriatrics, 2022)
Abstract Background Physical frailty is associated with increased risk of falls, hospitalisation and mortality. There is a dearth of information on physical frailty of older adults living in residential aged care. This study aimed to describe physical frailty in aged care residents and investigate possible determinants of frailty. Method A retrospective audit of resident records was undertaken across 14 residential aged care facilities. Data were extracted on all consenting residents who had completed measures relating to frailty (Short Physical Performance Battery SPPB; grip strength). All data of the first record of measures were extracted, resident characteristics, and the time from admission to assessment. Summary statistics were completed. Differences between sub-groups were explored (Mann-Whitney U, Kruskall-Wallis Ranked tests). Associations between variables were explored with Chi-squared and Pearson correlations. Determinants of physical frailty were determined with linear regression analyses. Alpha (2-sided) was 0.05. Results Data were extracted for 1241 residents (67% female), with a mean age of 86.0 (7.6) years. Males had a significantly lower time from admission to assessment of frailty (p ≤ 0.001). The average SPPB score was 4.1 (3.3), 75% of residents were frail and 19% pre-frail. Bivariate analyses indicated no significant relationships between grip strength and SPPB score, but significant differences for grip strength, where males were significantly stronger (males 20.2 ± 8.3 kg; females 12.4 ± 5.4 kg; p ≤ 0.001). There was a significant positive relationship between SPPB total score and grip strength, gender (p ≤ 0.001), and marital status (p = 0.049) and a negative relationship between time from admission to assessment and SPPB total score (p ≤ 0.001). There were significant negative relationships between gender (p ≤ 0.001) and age (p ≤ 0.001), and time from admission to assessment (p ≤ 0.001) with grip strength. Conclusion Older adults living in residential aged care have a high level of physical frailty which may lead to increased risk of adverse outcomes. Time in the residential aged care setting and age appear to predict physical frailty. There is a need for a consistent battery of measures to continually monitor frailty and programs to address the high levels of frailty in residential aged care.